Phase engineering in tantalum sulfide monolayers on Au(111). (1st April 2023) - Dombrowski, Daniela; Samad, Abdus; Mehlich, Kai; Chagas, Thais; Schwingenschlögl, Udo; Busse, Carsten
Abstract: We prepare monolayers of tantalum sulfide on Au(111) by evaporation of Ta in a reactive background of H2 S. Under sulfur-rich conditions, monolayers of 2H-TaS2 develop, whereas under sulfur-poor conditions TaS forms, a structure that can be derived from 2H-TaS2 by removal of the bottom S layer. We analyze the alignment of the layers with respect to the substrate and the relation with the domains in the Au(111) herringbone reconstruction using scanning tunneling microscopy. With the help of density functional theory calculations we can determine the registry of the two phases with the substrate. We develop a growth process that allows preparation of uniquely oriented 2H-TaS2 on Au(111). 2H-TaS2 and TaS have a remarkably similar in-plane lattice structure and we observe the formation of lateral 2H-TaS2 -TaS heterostructures with atomically well-defined and defect-free boundaries. We observe mirror twin boundaries within 2H-TaS2 along the S- and Ta-edge.